The complex challenge of sustainable architectural design: Assessing climate change impact on passive strategies and buildings’ opportunities for adaptation. A case study - Ganem Karlem, Carolina (2021)
As a response to the last century energy crisis, passive strategies have been an interesting approach. Nevertheless, there are limits to passive design. And these limits will be greater constraints to the maintenance of interior temperatures within acceptable parameters in future more extreme climatic conditions, even with the complementary use of auxiliary energy. The objective of this paper is to assess climate change impact on passive strategies and buildings’ opportunities for adaptation in different RCP extreme future conditions. The performed analyses on passive strategies show a clear tendency to the increment of cooling loads and a reduction of the heating requirement. Moreover, when heating and cooling needs are added in a single figure it is interesting to analyse the whole energy consumption trends. In the study case, as well as similar constructions, total energy consumption present a maximum variation of less than 10% when compared with the worst-case scenario 4: CRP 8.5 (2100). Even though these figures look alike, there is a significant change in the source. Today, energy consumption for heating (natural gas) accounts for 57.5% of the total. While, in the worst-case scenario 4: CRP 8.5 (2100, energy consumption for cooling (electricity) predominates with 77.8% of the total.